Developing professional capital in policy and practice: Ontario's Teacher Learning and Leadership Program. Issue 3 (4th July 2016) - Campbell, Carol; Lieberman, Ann; Yashkina, Anna
Abstract : Purpose: – The purpose of this paper is to provide evidence from Ontario's Teacher Learning and Leadership Program (TLLP) with goals to: support experienced teachers to undertake self-directed professional development; develop teachers' leadership skills for sharing their professional learning and practices; and facilitate knowledge exchange. Design/methodology/approach: – The paper draws on four years of research including: analyses of TLLP project application proposals and final reports; observations and participant feedback for TLLP events; surveys of TLLP project leaders; vignettes by teacher leaders; interviews with teachers, government and union leaders; case studies of TLLP projects; and analyses of TLLP online networking activity. Findings: – TLLP provides an example of developing professional capital, involving: changes in the style and substance of policy making concerning government and unions' approaches to teachers' professional development; and the experiences of teachers developing their individual and collaborative professional learning and leadership with benefits for teachers and for students. Originality/value: – Five implications are highlighted: prioritizing teachers' learning and leadership of, by and for teachers requires shifts in the substance and style of policy making for teachers' work; professional collaboration benefits from appropriate partnerships and an enabling system with conditions and support for teachers' learning and leadership; valuing and supporting teachers taking charge of their own professional learning is integral; developing teachers as leaders of their peers' learning and educational improvements is vital; and enabling teachers as developers of actionable knowledge is powerful for sharing improvements in practices.